A social-psychological study of resistance to family planning in rural Alabama - Sinquefield, Jeanne Cairns (Chicago : University of Chicago Press, 1974)
The interviews were designed and pretested during the summer of 1969, and the field work conducted from September 1969 to March 1970. The coding, keypunching, editing, and tabulation were completed in Fall 1970. The final draft was finished in September 1971. The manuscript, however, does not indicate all that was learned during the study. Equally important was the knowledge of what a single individual could do to improve the life of other human beings through dedication, and hard work.
Chapter One. Sources of resistance to innovations -- Chapter Two. the effect of personal efficacy on resistance to family planning -- Chapter Three. Family factors in resistance to family planning -- Chapter Four. The effect of a woman perception of the legitimacy of family planning on resistance -- Chapter Five. The effect of motivations for and instrumentality of family planning on resistance -- Chapter Six. A tentative model of resistance to innovation: the case of family planning.
Keywords: FAMILY PLANNING